1998
DOI: 10.1134/1.567875
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Do excited states exist in a system of two neutrons? [JETP Lett. 67, No. 11, 903–909 (10 June 1998)]

Abstract: This article consists of an error which was reported by the authors. Namely, the term ''deuteron'' was erroneously used throughout the article instead of a correct term ''dineutron.'' Therefore, below we offer a complete reprint of the article with the correction being incorporated. We apologize for the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…These complex eigenvalues coincide with the S matrix pole positions. This method was tested for three-body resonances in [10], and was applied to the low-lying spectra of the 6 He, 6 Li, and 6 Be nuclei in [11]. Further details and references of the method can be found there.…”
Section: Complex Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…These complex eigenvalues coincide with the S matrix pole positions. This method was tested for three-body resonances in [10], and was applied to the low-lying spectra of the 6 He, 6 Li, and 6 Be nuclei in [11]. Further details and references of the method can be found there.…”
Section: Complex Scalingmentioning
confidence: 99%
“…There are experimental indications of the possible existence of resonances in other A = 3 nuclei, too. For example, in a recent H( 6 He,α) experiment [6] the authors concluded that in order to explain their results, an excited state of the triton has to be assumed with E * = 7.0 ± 0.3 MeV excitation energy and Γ = 0.6 ± 0.3 MeV width.…”
Section: Introductionmentioning
confidence: 99%
“…The double charge exchange process on 3 He was also investigated in [5] criticizing previous work but pointing again to a 3n resonance, now around (20 − i 20) MeV. For the nnp system an excited state around 7 MeV with a width of Γ = 0.6 ± 0.3 MeV has been suggested in [6]. A variational study based on complex scaling and simplified nucleon-nucleon (NN) forces was carried through in [7] with the prediction of a 3n resonance at E = (14 − i 13) MeV for a J π = 3/2 + state.…”
Section: Three-nucleon (3n) Resonances Have Not Yet Been Firmly Estabmentioning
confidence: 99%
“…In the mirror 3 He nucleus the Ref. [5] experiment does not indicate an excited state. However, in a recent work [7] it was shown that the effective range function of the doublet d+p scattering has a singularity at a negative energy, just below the d + p threshold.…”
Section: Introductionmentioning
confidence: 97%
“…However, several calculations, mostly confined to small model spaces, indicate a virtual state in 3 H, and corresponding subthreshold resonances in 3 He. Recently, the authors of a H( 6 He, 4 He) experiment have claimed to find an excited state of 3 H at E * = 7 ± 0.3 MeV excitation energy with Γ = 0.6 ± 0.3 MeV width [5]. According to one interpretation [6] this is a 1/2 + excited state formed mainly in the (nn)p channel.…”
Section: Introductionmentioning
confidence: 99%